If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + x) + -1(5x + 2) = 3 Remove parenthesis around (1 + x) 1 + x + -1(5x + 2) = 3 Reorder the terms: 1 + x + -1(2 + 5x) = 3 1 + x + (2 * -1 + 5x * -1) = 3 1 + x + (-2 + -5x) = 3 Reorder the terms: 1 + -2 + x + -5x = 3 Combine like terms: 1 + -2 = -1 -1 + x + -5x = 3 Combine like terms: x + -5x = -4x -1 + -4x = 3 Solving -1 + -4x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 3 + 1 -4x = 3 + 1 Combine like terms: 3 + 1 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| (2x+3)(3x+4)=0 | | 29=2x+77 | | 4.75r+4.25= | | 35-9+4x=29 | | y+53=60 | | y=12x-17 | | -13f-4=-5f+52 | | 219=10 | | -1=4x+14y | | 6x=8y+10 | | 3X-27=-2X+8 | | 3/5=5r | | 148=2(10-5x)-12 | | -9(-5+x)=-108 | | 8(x-4)=4(x-13) | | 18/27=16/ | | 4p-5=8-2p | | 9y=-3x+5 | | 8=-4y-5x | | 1.5f=45 | | 7b-3b=18 | | 0.25+1.5=-3 | | 8=-4y-x | | (6x^4y)(12x^3y^9)= | | 7x^2+5x-13=35-29x | | Solvingx+2y=7 | | 8(5d-8)= | | -9(-5+x)=108 | | x+(5x-2)+(7x-4)= | | 3/6z=-4 | | 2X-26=-3X+9 | | 13j-1=7j+23 |